Effect of accelerated weathering on the strength properties of glulam produced from mengkulang timber treated with Light Organic Solvent Preservatives (LOSP) / Syarifah Hanisah Syed Mokhtarruddin - Syed Mokhtarruddin, Syarifah Hanisah (2019)
Glulam produced from low-grade timber should be treated to increase its durability against termites and insects' attacks when exposed to outdoor environment. The main objective of this work was to investigate the effect of a number of factors, namely Light Organic Solvent Preservatives (LOSP) as environmental friendly of timber preservative and accelerated weathering using QUV machine, which could be applied to compare solid beams and glulam beams in the strength properties. The samples then were treated using LOSP and then were subjected to accelerated weathering in accordance with ASTM G 154. The size of the solid beams and three-ply glulam beams is 50 mm(W)x60 mm (T)xl200 mm (L) as accordance with BS EN 408. Phenol resorcinol formaldehyde (PRF) resin was used as the adhesive for the manufacturing of glulam beam. The strength properties was measured through flexural strength test (in accordance with BS EN 408) over a range of Modulus of Rupture (MOR) and Modulus of Elasticity (MOE). Subsequently, the strength properties assessment by Block Shear Test and Delamination Test to measure the bonding strength of glulam beams (in accordance with MS 758). Chemical analysis on the penetration of LOSP into the timber was also investigated using high performance liquid chromatography (HPLC). Statistical analysis (ANOVA) was carried out to determine the effects of the variables on the strength properties of solid timber and glulam. The results revealed that the MOR value after flexural strength test showed a decreasing pattern for both solid beams and glulam beams after being treated with LOSP. The same pattern also repeated for flexural strength test in solid beams and glulam beams after accelerated weathering. Indeed, the same pattern goes to solid beams and glulam beams treated with both factors. Comparison between solid beams and glulam beams showed that the strength values of solid timber beams are extensively decreasing in strength value after all the treatment. However, glulam showed a different pattern, in which gradually decreasing after all the treatment. This supports that glulam beams performed better and more stable than solid timber beams. Glulam in this study showed good bondability between the wood and resin after being treated with LOSP and undergo accelerated weathering. It was found that wood failure resulting from shear strength achieved approximately 90 %. Delamination of glue line in this study was acceptable as it was in the range of 5.49 % to 12.39 %. Thus, glulam shows a good bondability between timber and adhesive after being treated with LOSP and undergo accelerated weathering. In conclusion, all glulam beams with and without LOSP treatment and accelerated weathering passed the criteria of Malaysian Standard for glulam timber.